Latar Belakang Penulisan Prasasti Tandihat II Pada Paha Kiri Depan Arca Singa - Churmatin Nasoichah (Berkala Arkeologi Sangkhakala, 2008)
AbstractOne of the Buddhist inscriptions which discovered in Sumatera is Tandihat II inscription. Between inscription it self with the lion statue as a medium, certainly have a special connection.